(untitled) (Bangladesh Pharmaceutical Journal, 2019)
The present investigation was design for domperidone floating table preparation and in-vitro characterization. The ultimate target was increasing gastric retention by means of floatability of the tablet. Hydrophilic cellulosic polymers, Methocel K15M and Methocel K100M were used in this experiment for achieving release controlling property. Sodium bicarbonate played the key role of floatation by generating gas. Direct compression was the method of choice for preparing the tablets. The tablets were evaluated for physical parameters, buoyancy study, total floating time determination and dissolution study. Acidic dissolution medium (0.1N HCl), mimicking the environment of the stomach, was used in USP II apparatus for 12 hours to find out the pattern of drug release. The release mechanism was analyzed by exploring the zero order, first order, Higuchi and Korsmeyer equations. All the physical parameters were within acceptable range and Methocel K100M showed more floating lag time and sustained release property than Methocel K15M. All the formulations showed more than 12 hours floating time. Fourier Transform Infrared Spectroscopy (FTIR) study confirmed the compatibility of the drug with the excipients. Bangladesh Pharmaceutical Journal 22(2): 170-175, 2019